Trafficking, Scandal, and Abuse of Migrant Workers in Argentina and the United States. Issue 1 (May 2014) - Brennan, Denise
This article examines the varied consequences that the label "trafficked" holds for migrants and for the organizations that assist them. In the case of migrants from the Dominican Republic to Argentina, threat of U.S. economic sanctions prompted the two governments to document incidents of trafficking by labeling all forms of migrant labor exploitation as trafficking. Collapsing a range of coerced and noncoerced labor experiences under one label has muddied the definition of trafficking. In contrast, U.S. trafficking policy systematically ignores significant exploitation of labor migrants, in part because of the volatile politics of immigration in the United States, and because of the conflation of sex trafficking with trafficking. The article uses these two examples of the effects of labeling exploited workers as trafficking victims to draw attention to the politicization of the term "trafficking."